Global, regional, and national burden and trends of HIV/AIDS among women of childbearing age from 1990 to 2021: results from Global Burden of Disease 2021 - Tang, Mingjie; Shao, Jun; Jiang, Yanjie; Li, Yinghong; Li, Shiwei; Song, Yilin; Wu, Wenxuan; Tang, Jiqin; Chen, Zhaoming (Frontiers in Medicine, 2025)
BackgroundHuman immunodeficiency virus (HIV) is one of the key factors contributing to global morbidity and mortality. Women of childbearing age (WCBA) represent a high-risk population for HIV/AIDS, presenting a substantial challenge to global public health systems. A comprehensive understanding of the AIDS burden in this demographic is essential for developing targeted screening and treatment strategies to effectively control mother-to-child transmission.MethodsUtilizing GBD 2021 data, this study systematically evaluated epidemiological trends in HIV/AIDS incidence, prevalence, mortality, and disability-adjusted life years (DALYs) among WCBA. The analysis employed a multidimensional stratification approach, examining temporal patterns, age distributions, geographic variations, and Socio-demographic Index (SDI). Additionally, a comprehensive analytical approach was employed, which included the estimated annual percentage change (EAPC), Joinpoint regression, decomposition analysis, and predictive modeling using the Nordpred method. Decomposition analysis quantified contributions from population growth, aging, and epidemiological changes.ResultsFrom 1990 to 2021, the numbers of incidence, prevalence, mortality, and DALYs of HIV/AIDS among WCBA increased significantly. In 2021, the global age-standardized rates for incidence (ASIR), prevalence (ASPR), mortality (ASMR), and DALYs (ASDALYR) were 34.73 (95% uncertainty interval [UI]: 30.03 to 40.54) per 100,000, 830.87 (95% UI: 784.57 to 884.29) per 100,000, 13.39 (95% UI: 10.34 to 17.56) per 100,000, and 829.75 (95% UI: 658.24 to 1,063.9) per 100,000, respectively. ASIR showed a downward trend, while ASPR exhibited an upward trend. Geographically, the highest persistent burden was observed in Sub-Saharan Africa. High-middle SDI region, Eastern Europe, and Pakistan had the fastest growth in incidence. Decomposition analysis showed that the increase in HIV/AIDS indicators among WCBA was mainly caused by population, and epidemiological changes. Nordpred analysis predicts modest decline in ASIR, ASPR, and ASMR by 2046.ConclusionFrom 1990 to 2021, substantial rise in incident cases, prevalent cases, mortality, and DALYs has established HIV/AIDS among WCBA as a critical global public health burden. This burden exhibits marked disparities across geographic regions, countries, and age groups. In high-burden areas, particularly Sub-Saharan Africa, public health practitioners must strengthen international cooperation and prioritize expanding HIV testing and antiretroviral therapy access, women’s empowerment, and removing socio-cultural barriers.